2015
DOI: 10.18673/gs.v6i2.22487
|View full text |Cite
|
Sign up to set email alerts
|

Atemdimel - apoio telefônico para o monitoramento em diabetes mellitus tipo 2: expectativas e satisfação dos pacientes

Abstract: Estudo observacional, quali-quantitativa, avaliou as expectativas e satisfação de pacientes que receberam suporte telefônico para o monitoramento do DM. A população foi de 45 diabéticos, 18 do grupo intervenção e 27 do grupo controle. O projeto foi aprovado no Comitê de ética, parecer 324.098. Os dados foram obtidos por questionários subdivididos em três partes. A primeira, contendo variáveis sociodemográficas e clínicas; sendo em ambos os grupos com predomínio do sexo feminino; estado civil foi o casado; esco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Telephone follow-up, in addition to providing information and clarifying patients' questions, increases the satisfaction of those who receive care (21) . Thus, a study demonstrated a high patient satisfaction regarding telephone monitoring, making professionals perfect their intervention techniques (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Telephone follow-up, in addition to providing information and clarifying patients' questions, increases the satisfaction of those who receive care (21) . Thus, a study demonstrated a high patient satisfaction regarding telephone monitoring, making professionals perfect their intervention techniques (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Assim, corroboram-se este estudo pesquisas que aplicaram a intervenção telefônica com diabéticos, as quais obtiveram resultados satisfatórios, mostrando que os participantes apresentaram melhorias no conhecimento, na prática de autocuidado e satisfação com as ligações, tendo as expectativas atendidas (15)(16)(17) .…”
Section: Discussionunclassified
“…16 The nurse, when assisting this public, must consider the biopsychosocial aspects of the user, so that actions in the health-disease process become effective and user satisfaction is guaranteed through precision in care and humanized attention. [16][17] Thus, user satisfaction with the care received contributes significantly to the maintenance of their health, also taking into account, which favors adherence to their treatment, among other factors. 11…”
Section: [] What I Wanted To Change Was If the Government Gave Us The Medicines We Could Take Because I Took And My Medicines Were All Chmentioning
confidence: 99%